Pertumbuhan dan Hasil Kedelai dengan Aplikasi Limbah Tofu dan Mikoriza Arbuskular pada Tanah Masam - Wan Arfiani Barus; Bambang S.A.S; Bagus Permadi (Agrotechnology Research Journal, 2019)
Utilization of acid soils for food crop development must be carried out because of land conversion. The main problem in acid soils is the unavailability of P nutrients. Utilization of Arbuscular Mycorrhiza on acid soils has been found to contribute to the availability of P nutrients. This study used a factorial randomized block design with 2 factors, namely the application of tofu waste and arbuscular mycorrhiza. Tofu waste dosage consists of 0, 125, 250 and 375 g/polybag and Arbuscular Mycorrhiza application, namely: 0, 6, 12 and 18 g/polybag. The results showed that the application of tofu waste at a dose of 375 g / polybag affected significantly and gave the best results for the parameters of plant height, number of branches, wet weight and dry weight of soybean crop stover. While the application of arbuscular mycorrhiza with the best dose of 18 g / polybag affected significantly to fresh weight and dry weight of the roots of soybean. However, the interaction between the two treatments did not affected significantly to all observed variables.